Pemahaman Konsep Matematis Siswa : Systematic Literature Review (SLR) - Imelda Verina; Dadang Juandi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
This study aimed to describe the research results related to students’ conceptual understanding in mathematics analyzed based on their learning style. The method used in this study was Systematic Literature Review (SLR). The sample consists of 17 articles indexed in SINTA and Google Scholar, published in 2018 until October 2022, and located in Indonesia. The description in this study will be reviewed based on the year of publication, journal indexes, method uses, level of education, number of subjects, subject matters, research locations, and the theory used in learning style. Through the SLR method, it was found that there was an increasing and decreasing in the number of articles, there were dominantly published in Google Scholar, qualitative method was dominant, the research conducted in junior high school dominant, 14 out of 17 researchers used less than 30 subjects, algebra was dominant followed by geometry and measurement, the research was dominant conducted in Java, DePorter and Hernacki theory were dominantly.